PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATA PELAJARAN IPS KELAS VIII SMP NEGERI 4 PITU RIAWA KAB. SIDENRENG RAPPANG - Karmila; Pattaufi; Andromeda Valentino Sinaga (STKIP Subang, 2024)
The development of digital technology today has a significant impact on world of education. The use of technology facilitates the process of learning and creating The learning atmosphere is not boring and monotonous. This study uses R&D (Research and Development) research and development methods. This study Aims to 1) Know the level of learning video media needs, 2) Design learning video media, 3) knowing the validity / feasibility of learning video media, 4) Know the level of practicality of learning video media. This research was developed by using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at SMP Negeri 4 Pitu Riawa Sidenreng Rappang District. The subjects of this study were 20 grade VIII students, 1 person teacher, and 2 validators consisting of material/content validators and media validators. Data collection using needs identification questionnaire, material/content validation questionnaire, media validation questionnaire, individual trial questionnaire, large group/field trial questionnaire and questionnaires of subject teacher responses. The results of this study are: 1) Results obtained from identifying the level of student needs to be in the required category, 2) Design learning video media using the Doratoon application, the resulting product in the form of an animated video containing the opening, content of the material and practice questions, 3) Results obtained from material / content validation and media validation is in the very valid category, 4) to test The level of practicality of the product is carried out individual trials, large group / field trials and teacher responses. From individual trials and teacher responses are in the very category Good while in large group / field trials are in the good category. Based on the results of this study, it can be concluded that the product has been developed by researchers is valid / feasible and practical to use in the learning process.